1999
DOI: 10.1046/j.1365-2605.1999.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of testicular tissue as a minced suspension preserves sperm quality better than whole‐biopsy freezing when glycerol is used as cryoprotectant

Abstract: Frozen-thawed testicular spermatozoa have been used successfully for ICSI, especially in cases of obstructive azoospermia with normal spermatogenesis. Fewer attempts, however, have been made to check whether these rather immature spermatozoa, in a different environment with several other cell types present, have cryobiological requirements other than those of ejaculated spermatozoa. This is the reason why the freezing protocols and cryoprotectants (glycerol) used for freezing testicular tissue are based on exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…We expected to have higher number of cells survive in smaller size testis fragments compared to larger fragments or intact testes. It has been reported that spermatozoa could be better cryopreserved in minced tissues than in larger tissue biopsies (Crabbé et al 1999). Tissue sizes ranging from 0.5 to 1.5 mm 3 are routinely used for testis cryopreservation (Abrishami et al 2010;Zeng et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We expected to have higher number of cells survive in smaller size testis fragments compared to larger fragments or intact testes. It has been reported that spermatozoa could be better cryopreserved in minced tissues than in larger tissue biopsies (Crabbé et al 1999). Tissue sizes ranging from 0.5 to 1.5 mm 3 are routinely used for testis cryopreservation (Abrishami et al 2010;Zeng et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Fazla kriyoprotektan kullanımının ise hücrelerde toksik etkinin artmasına neden olduğu bildirilmektedir [28]. Ayrıca, testisin hücre süspansiyonu şeklinde dondurulmasının doku olarak dondurulmasına kıyasla, hücre canlılığını daha iyi koruduğu da belirtilmektedir [29]. Bu nedenle, çalışmamızda prepubertal testis dokusunu hücre süspansiyonu olarak dondurmayı tercih ettik.…”
Section: Discussionunclassified
“…The median age of spermarche is estimated to be around 13 to 14 years, with a range between 11 and 17 years [36,37]. Thus, we recommend searching for testicular sperm in specimens from all boys aged 10 years or older, since freezing testicular sperm in glycerol-based medium [38] for use in ICSI is available in most ART laboratories [39]. Protocols for freezing small samples (2 to 4 mm 3 ) of immature human testicular tissue using dimethyl sulfoxide (DMSO) as the main cryoprotectant showed good structural integrity of testicular tubules, and pre-tubular and intra-tubular cells after thawing [11,40].…”
Section: Testicular Tissue Biopsy and Cryopreservationmentioning
confidence: 99%